Built environment and crime: defensible space - housing in Malaysia / Prof Madya Dr Mohamed Yusoff Abbas, Ida Noorjulianti Sugijanto and Prof Madva Dr Mizan Hitam - Abbas, Mohamed Yusoff; Sugijanto, Ida Noorjulianti; Hitam, Mizan (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2006)
This study is about crime trends with focus on housebreaking which occurred in Malaysia nationwide between the years 1994-2004. The purpose being to trace the trend and identiS the paffern, manner and factors involved with housebreaking so that preventive measures could be suggested.